Method of determining the normal modes of toothed gears with complex geometry - Stanisław NOGA; Tadeusz MARKOWSKI; Roman BOGACZ (Scientific Journal of Silesian University of Technology. Series Transport)
This work deals with transversal vibrations of the toothed gear, which is discussed as an annular plate with a complex geometry. The procedure for determining the proper distorted normal modes of vibrations of the wheel with discontinuous geometry is discussed. The required models are created by means of the finite element method. The pre–stress effect is included by means of the ANSYS code. The problem of modelling utilizing cyclic symmetry of the system under study is discussed. It is important to note that the issues presented in this work have a practical value for design engineers dealing with the dynamics of rotating systems.